A simple, low cost, and template-free method for synthesis of boron nitride using different precursors. Issue 5 (1st March 2021) - Mirzaee, Majid; Rashidi, Alimorad; Zolriasatein, Ashkan; Rezaei Abadchi, Majid
Abstract: In this research, hexagonal boron nitride (h-BN) was synthesized using a simple, low cost, and template-free method with urea-boric acid (UB), melamine-boric acid (MB), and melamine-urea and boric acid (MUB) precursors, followed by the pyrolysis and heat treatment in a nitrogen atmosphere at 1050 °C. Samples were characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), X-ray photoelectron spectroscopy (XPS), Raman Spectroscopy, Fourier transform IR (FT-IR), and Brunauer–Emmett–Teller (BET) techniques. The specific surface areas obtained for h-BN synthesized by UB, MB, and MUB precursors were 87.43, 573.07, and 1005.7 m 2 /g, respectively. The average diameters of the pores using the Barrett, Joyner, and Halenda (BJH) model were 37.78, 3.68, and 2.13 nm, respectively. A thermogravimetric analysis showed a wider range of decomposition temperatures after using three precursors for synthesizing h-BN. Crumpled, whisker, and flower-like morphologies for UB, MB, and MUB precursors were respectively found using FESEM investigations. The formation of h-BN within the MUB sample was confirmed using the XPS analysis with measured peaks of 398.5 and 190.6 eV belonging to N 1s and B 1s, respectively. Raman spectroscopy revealed a high-intensity peak in 1366 cm −1 related to the E2g mode for h-BN synthesized with MUB. Therefore, the results demonstrate that the employed method can increase the potential of using the h-BN porous powder with a high specific surface area as a lubricant, thermal insulation filler, anti-corrosion filler in paint coatings, adsorption of various gas and hydrocarbon molecules as well as its application in drug-delivery nanocarriers.